Evaluasi program Makassar Ta’ Tidak Rantasa di Kota Makassar - Muh. Nur Yamin; Muhammad Guntur; Herlina Sakawati (Seminar Nasional LP2M UNM, 2019)
Makassar Tidak Rantasa (MTR) Program Evaluation Research in Makassar City aims to determine the consequences of a policy by describing its impact, and to assess the success or failure of a policy based on established standards. Critical and in-depth assessment because public policy is a policy process by the government that has an impact on the wider community. The design of policy evaluation study research uses a qualitative descriptive approach with data collection techniques using interviews and observations. Determination of informants used a purposive technique in a number of policy implementing informants and target communities at the sub-district level in the Makassar City area. Technical data analysis of interactive models from Miless, Hubermann and Saldana. The results showed the success of the program in the MTR Movement in the form of the Lisa movement and Sekolahku movement had gone well even though the Mabasa movement and the Mabelo movement had not gone well. The level of effectiveness of the MTR program seems to be inadequate in terms of program effectiveness, efficiency, and adequacy, compared to aspects of equity, accuracy and responsiveness have been implemented well. The implementation of the Makassar No Rantasa Program was generally carried out well with constraints on the factors of community understanding and infrastructure that were still unfavorable so that the response of a small part of the community was still not good. This study recommends assessments of suitability, testing and evaluating the ongoing MTR policy suitable to be maintained but requires a firm attitude from the city government to enforce the rules on cleanliness and waste management.